A framework to monitor crop-specific drought and flood impacts using remote sensing datasets - Pun, M.; Shrestha, Nirman; Schmitter, Petra S.; Zemadim, Birhanu (International Water Management Institute (IWMI). CGIAR Initiative on Excellence in Agronomy, 2023)
Weather triggered hazards such as drought and flooding have negative impacts on society and agriculture. Drought can lead to reduced access to drinking water, lower agricultural productivity, and conflicts over water resources. Flooding causes loss of agricultural production, damages infrastructure, and leads to socio-economic losses. The report aims to develop a guiding framework to create a Combined Drought and Flood Index (CDFI) for monitoring crop-specific agricultural drought and flood conditions. The proposed framework for monitoring crop-specific agriculture drought and flood conditions includes meteorological, agricultural, and hydrological indices. The framework uses remote sensing datasets to monitor drought and flood impacts. The cross-referencing of these indices helps reduce the probability of false alarms during monitoring floods and droughts. It is crucial having a uniform methodology that countries can apply to monitor drought and flood conditions for specific crops. The 5-step standardized methodology was applied for the case study country in Ethiopia, where wheat, sorghum, and teff crops are the major crops. The findings show, flooding occurred in the northern and central part of the country in 2016, causing reduced respiration in the soil root zone of crops affecting mid-season phenological growth of sorghum, wheat, teff, and barley. Likewise, the study revealed, in 2015 moderate to severe drought impacted the phenological growth of sorghum due to the El Nino Phenomenon. The framework aims to provide valuable insights for policymakers, decision-makers, and agricultural practitioners. The coarse resolution of the rainfall and soil moisture datasets applied in the study might be limitations of this method however, it still provides a valuable oversight for agricultural drought and flood monitoring.